FISIOLOGIA REPRODUTIVA EM OVELHAS – BREVE REVISÃO - Lemes, Laura Queiroz; de Lima, Isadora; Alves, Bruna Farias; Travi, Magdalena Reschke Lajús; Carneiro, Maico Fernando Wilges; Daneluz, Marina Oliveira (Anais de Medicina Veterinária; v. 2 n. 1 (2022): 2022/2, 2022)
.